The Student Cognitive Load in Teaching and Learning of Plant Tissue Using the Time-Based Resource Sharing Model - Febriani, Maya Amelia; Rahmat, A.; Nuraeni, E. (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
One of the successes teaching and learning can reduce students’ cognitive load. The principle of applying cognitive load theory is using working memory which can be managed by a cognitive treatment through refresh memory from the psychological model of the Time-Based Resource Sharing Model (TBRS Model). The research method used is preexperiment was aim to determine students’ cognitive load in teaching and learning of plant tissue using the TBRS model. The total cognitive load consists of Intrinsic Cognitive Load (ICL) measured by task complexity worksheet, Extraneous Cognitive Load (ECL) measured by subjective rating scale, Germane Cognitive Load (GCL) measured by the cognitive system level 2 dan 3 (Marzano & Kendal, 2007), and interview as secondary data. The participants were 36 science students of Senior High School. The bivariate correlation test showed correlation between ECL and GCL is positive but not significant (0,171; α > 0.05); ECL and ICL is positive but not significant (0,073; α > 0.05); ICL and GCL is negative but not significant (- 0,104; α > 0,05). From these data, the formation of students' cognitive schemes described GCL is not clearly influenced by ICL or ECL so students still have a cognitive load. The results of student interviews showed this cognitive load does not consequence by the TBRS model but from the other factors such as difficult material and material presented partially. In addition, this situation also supported by the results of a questionnaire showed that students helped by refresh memory in the TBRS model. So there is still a cognitive load on students not due to malfunction of the TBRS model but due to other factors that have been explained above